The Basal Ganglia and Motor Control - Henk J. Groenewegen (Neural Plasticity)
This paper briefly reviews the functional anatomy of the basal ganglia and their relationships with the thalamocortical system. The basal ganglia, including the striatum, pallidum, subthalamic nucleus, and substantia nigra, are involved in a number of parallel, functionally segregated cortical-subcortical circuits. These circuits support a wide range of sensorimotor, cognitive and emotional-motivational brain functions. A main role of the basal ganglia is the learning and selection of the most appropriate motor or behavioral programs. The internal functional organization of the basal ganglia is very well suited for such selection mechanisms, both in development and in adulthood. The question of whether clumsiness may be, at least in part, attributed to dysfunction of the basal ganglia is discussed in the context of the differential, complementary, or interactive roles of the basal ganglia and the cerebellum in the development of motor control.